Emergency Department Management of Febrile Respiratory Illness in Children. Issue 7 (July 2016) - Shah, Sonal; Bourgeois, Florence; Mannix, Rebekah; Nelson, Kyle; Bachur, Richard; Neuman, Mark I.
Abstract : Background: There are limited data regarding testing and treatment patterns for children presenting to the emergency department (ED) with a febrile respiratory illness. Objectives: The aims of the study were to evaluate the rates of diagnostic testing, antibiotic use, and pneumonia diagnosis among children presenting to an ED with a febrile respiratory illness and to evaluate whether differences exist on the basis of care at a pediatric versus a general ED. Methods: Cross-sectional study of children presenting to an ED with a febrile respiratory illness from 2001 to 2010 used the National Hospital Ambulatory Medical Care Survey. Using extrapolated estimates from the weighted population sample, rates of laboratory and radiographic testing, antibiotic use, and pneumonia diagnosis were ascertained. Comparisons were made between children treated at a general versus pediatric ED. A subpopulation of children undergoing chest radiograph was identified to target those with concern for radiographic pneumonia. Results: Fifteen percent of the 12 million visits for febrile respiratory illness occurred in a pediatric ED. Thirteen percent (95% confidence interval [CI], 11–15) of patients had a complete blood count, 4% (95% CI, 3–5) had a blood culture, and 33% (95% CI, 30–35) had a chest radiograph obtained; no differences were observed on the basis of ED type. Despite similar rates of pneumonia diagnosis, antibiotics were prescribed less often for children cared for in a pediatric (35% [95% CI, 30–41]) versus general ED (50% [95% CI, 47–53]). Similar findings were observed among the subgroup of children with febrile respiratory illness undergoing chest radiograph. Conclusions: High rates of diagnostic testing were observed among children with febrile respiratory illnesses, despite low rates of pneumonia diagnosis. Antibiotic use was higher among children cared for at a general ED compared with pediatric ED.